REFORMASI KITAB UNDANG-UNDANG HUKUM PIDANA DALAM PENANGGULANGAN TINDAK PERUNDUNGAN DI INDONESIA - Fenti Darna Pradewi (Jurnal Ilmiah Advokasi, 2026)
This study examines the legal response to the increasing incidence of bullying in Indonesia. The study aims to analyze the regulatory framework governing bullying in the national Criminal Code (KUHP) and to evaluate the application of restorative justice principles in its handling. The research employs a normative juridical method with statutory and comparative approaches; data sources include legislation, legislative drafting records, judicial decisions, and secondary literature; analysis is qualitative. Findings indicate that the National Criminal Code clarifies the legal basis for addressing bullying through provisions on insult, assault, threats, and cyber-related offenses, and creates space for diversion and restorative justice practices (e.g., out-of-court settlement clauses). However, implementation of restorative justice faces significant obstacles, including victim resistance, insufficient dissemination, and limited capacity of law enforcement agencies. This study contributes theoretically by formulating an analytical framework that integrates restorative justice principles into the interpretation of the National Criminal Code provisions on bullying, that intended to improve the effectiveness of bullying prevention and response in Indonesia.Keywords: Bullying; Indonesian law; Restorative justice; Reform of the Criminal Code.